Analisis Faktor K3 yang Bepengaruh Terhadap Produktivitas di Industri Otomotif - Aprianto, Tri; Setiawan, Bambang; Nuryono, Arif (Proceeding Mercu Buana Conference on Industrial Engineering, 2023)
The increasing development of industry and technology has the potential to cause a source of danger. In addition, work environment factors that do not meet Occupational Safety and Health (OHS) requirements, unsafe work processes, and increasingly complex work systems can pose a distinct threat to worker safety and health. This study aims to analyze the K3 factors that affect the decline in productivity. This study uses Focus Group Discussion to analyze problems and provide suggestions for improvement. The results of the analysis using Why-Why Analysis to find out the dominant causes show that OHS is considered a shackle. OHS equipment that is not provided according to potential hazards, OHS policy does not guarantee occupational safety and health, lack of firmness from companies in applying sanctions to violators of OHS regulations. This study concludes that by analyzing the factors regarding OHS Culture, OSH Training, and Employee Performance that influence productivity can be identified. With RCFA with Why-Why Analysis the company can make improvements to production declines.